1989
DOI: 10.1111/j.1348-0421.1989.tb00957.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective Immunity Induced by Porin in Experimental Mouse Salmonellosis

Abstract: The induction of protective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
1
19
1
Order By: Relevance
“…But TH1 cells also exert a protective role through direct cytotoxic activity against infected macrophages. Native porin isolated from S. enterica serovar Typhimurium induced the secretion of IL-2 from BALB/c splenocytes (26) and IFN-␥ from BALB/cByJ splenocytes (43) levels of which were not reduced by coculturing with polymyxin B (not attributable to LPS). With purified porin preparations of S. enterica serovar Typhi, pretreatment of mice with porin prior to inoculation with an unrelated antigen not only enhanced antigen-specific cellular immunity as demonstrated by a positive delayed-type hypersensitivity response but also enhanced the level of antigen-specific serum IgG2a (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But TH1 cells also exert a protective role through direct cytotoxic activity against infected macrophages. Native porin isolated from S. enterica serovar Typhimurium induced the secretion of IL-2 from BALB/c splenocytes (26) and IFN-␥ from BALB/cByJ splenocytes (43) levels of which were not reduced by coculturing with polymyxin B (not attributable to LPS). With purified porin preparations of S. enterica serovar Typhi, pretreatment of mice with porin prior to inoculation with an unrelated antigen not only enhanced antigen-specific cellular immunity as demonstrated by a positive delayed-type hypersensitivity response but also enhanced the level of antigen-specific serum IgG2a (1).…”
Section: Discussionmentioning
confidence: 99%
“…Although Matsui and Arai (26) demonstrated that passive transfer of T cells from BALB/c mice immunized with S. enterica serovar Typhimurium porins resulted in protection against salmonellosis in naive mice, the protective epitopes were not identified. Purified porin monomers and trimers are capable of inducing T-cell proliferative responses, as measured by in vitro [ 3 H]thymidine uptake assays (29,46), and elicit strong delayed-type hypersensitivity reactions when inoculated into mice (26,49). However, the difficulty of preparing purified porin which is free of lipopolysaccharide (LPS) contamination raises questions as to whether the observed responses were specific for the porin component of the inoculum.…”
mentioning
confidence: 99%
“…The physical shielding of surface epitopes by the LPS implies that the immunoprotection observed by immunization of mice with anti-porin antibodies in previous studies (26,27,33,50) may have resulted from contaminating anti-LPS antibodies. OM protein epitopes may be transiently exposed at the cell surface, however, as a consequence of natural turnover of cell wall materials during certain periods (e.g., biogenesis of OM) in the life cycle of bacterial cells (12).…”
Section: Methodsmentioning
confidence: 99%
“…The function of buried epitopes, or antisera against them, in host defense against bacterial infection is not known. Aside from this gap in the understanding of immunity to bacteria, it is known that humoral immunity to infection by the Enterobactenaceae consists in part of antibodies to OM proteins (6,8,13,42) and that purified OM proteins elicit protective immunity in animals (5,17,21,26,27,33,51,56).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that immunity to Salmonella infection can be transferred with T cells alone in these mice (24,31,32). However, others have suggested that T cells are not sufficient (5).…”
mentioning
confidence: 99%